Labor Supply and Matching Rates for Welfare Recipients: An Analysis using Neighborhood Characteristics - Bas van der Klaauw; Jan C. van Ours (Tinbergen Institute, 2000)
This paper investigates how in addition to personal characteristicstheneighborhood affects the individual transition rate from welfare towork.We use a unique administrative database on welfare recipients inRotterdam,the second largest city of The Netherlands. We find that the exitrate towork of young Dutch welfare recipients is influenced by theneighborhoodunemployment rate. Other neighborhood characteristics such as theaveragehousing price are not important. From this we conclude that for youngDutchwelfare recipients a high local unemployment rate has a negativespillovereffect on the transition from welfare to work.
Keywords: 330; Arbeitsangebot; Öffentliche Sozialleistungen; Rotterdam